Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan di Toko Inti Tani Utama Sambi - Alvendho Mauliwarma Dewa Ihza; Ruslan Shomad (JMK (Jurnal Manajemen dan Kewirausahaan), 2022)
Customer satisfaction is very important for business development. Inti Tani Utama Sambi Agricultural Store is one of the shops in the agricultural sector that has problems with poor service quality and too expensive prices. This makes the customer feel unsatisfied. This study uses quantitative techniques with descriptive analysis. The sampling technique used is accidental sampling using the Slovin formula. The number of samples from this study were 83 respondents who were customers at the Inti Tani Utama Sambi Agricultural Store. The data in this study were obtained through observation, interviews and questionnaires. From the analysis that has been done using SPSS for Windows 16.0, the results show that service quality has a partial effect on customer satisfaction, price has a partial effect on customer satisfaction, service quality and price have a simultaneous effect on customer satisfaction. This is evidenced by the results of R Square of 0.893 or 89.3% and the remaining 10.7% is influenced by other variables outside the study.